Essays on Politics and Society - Carlyle, Thomas (The Norman and Charlotte Strouse Edition of the Writings of Thomas Carlyle Ser., 2022)
Essays on Politics and Society brings together the most significant writings on the topic by the acclaimed Victorian historian, social critic, and essayist Thomas Carlyle. This volume includes some of his most well-known and influential pieces, such as ""Characteristics"" and ""Chartism."" In keeping with the Norman and Charlotte Strouse Edition of the Writings of Thomas Carlyle, these essays are accompanied by a thorough historical introduction to the material, extensive notes providing historical and cultural context while expanding on references and allusions, and a textual apparatus that c.